Bio-inspired underwater robots powered by electroactive polymer artificial muscles - Chen, Zheng (Kansas State University, 2013)
Autonomous underwater robots are highly demanded in environmental monitoring, intelligent collection, and deep water exploration. Aquatic animals (e.g., fishes, whales, rays, etc.) are ultimate examples of superior swimmers as a result of millions of years of evolution, endowed with a variety of morphological and structural features for moving through water with speed, agility, and efficiency. Recent years have also witnessed significant effort in development of bio-inspired underwater robots to mimic aquatic animals, such as robotic fish, robotic jelly fish, and robotic manta ray. In most of these robots, traditional electric motors were used to generate rotation motions. However, since flapping motions are normally adapted by aquatic animals for maneuvering and propulsion, power transmissions are needed to translate rotation to flapping. These electric motors and power transmissions are too bulky to be embedded into small scale bio-inspired robots. Novel actuating materials, which are light, soft, and capable of generating large flapping motion under electrical stimuli, are desirable to build energy efficient and highly maneuverable bio-inspired underwater robots. Electroactive polymers (EAPs) are emerging smart materials that generate large deformations under electrical stimuli. EAPs have different configurations. Ionic Polymer-Metal Composites are important category of EAPs, which can generate large bending motion under low actuation voltages. IPMCs are ideal artificial muscles in small scale bio-inspired robots. A systems perspective is taken in this research, from modeling, control, and bio-inspired design. This presentation will be organized as follows. First, a physics-based and control oriented model of IPMC actuator will be discussed. Second, a bio-inspired robotic fish propelled by IPMC caudal fin will be presented and a steady-state speed model of the fish will be developed. Third, a bio-inspired robotic manta ray propelled by two IPMC pectoral fins will be demonstrated. Fourth, a buoyancy control device powered by IPMC enhanced electrolysis will be discussed. Last, advantages and challenges of using IPMC artificial muscles in bio-inspired robots will be concluded.
Keywords: Underwater robots; Electroactive polymers; Ionic polymer-metal composites; Artificial muscles